Complexities of Social Capital in Boards of Directors - Iwona Sulinska (Copenhagen Business School (CBS), 2018)
The aim of the dissertation is to disentangle complexities of social capital in boards of directors through proposing new theoretical perspectives and methodological approaches. Although extant previous research has discussed various aspects of social capital and its association with numerous organizational outcomes, still the literature demonstrates evident shortcomings resulting from overlooking and oversimplifying its complexities. Therefore, to fill gaps in the literature, the dissertation addresses the following research question: in the context of boards of directors, how can social capital be better understood through exploration of its complexities? The dissertation comprises three empirical studies that individually address the identified gaps in the literature and combined address the aforementioned research question. In this way, the dissertation demonstrates that social capital in boards of directors is more complex than it has been assumed in previous studies and its understanding requires a novel approach to conceptualization and empirical research. The first chapter explains the topic and motivation for the dissertation. The following chapter (Chapter 2) synthetizes the previous approaches to investigating board social capital and proposes a new theoretical and methodological approach. It particularly asserts that research on board social capital may be advanced through utilizing configurational perspective and method, what is then shown on an example of the relationship between board social capital and firm performance. Chapter 3 explores social capital of board chair, which has been overlooked in previous studies. It suggests that individual social capital of board chair is as important for organizational performance as social capital of CEO and directors. Therefore, performance effect derives from combined social capital of board chair, CEO, and directors. Further, the dissertation discusses dynamics of board social capital (Chapter 4) in the context of firm expansion. It emphasizes that evolution process of board social capital is driven by multidimensional changes occurring within internal and external networks of social relationships created by board members. Evolution paths are consequently proposed for diversity and strength of external network ties, and for internal network cohesion. In light of the overarching research question, the final chapter summarizes the findings.
hdl:10398/9606
Keywords: 650